Mobility of nanofiber, nanorod, and straight-chain nanoparticles in gases. Issue 5 (4th May 2017) - Tian, Lin; Ahmadi, Goodarz; Tu, Jiyuan
ABSTRACT: With the fast development of nanotechnology, accurate measurement and classification of nanoparticles are in great need. Nanoparticles frequently appear in non-spherical forms such as long aspect ratio nanofibers, nanotubes, and irregular nano-agglomerates. While the well-developed classical studies were mainly in continuum regime with spherical particles, dynamics of the non-spherical nanoparticles is not fully understood. In this study, orientation-averaged mobility of nanofiber and nanorod (with no preferred alignment) is examined by the methods of Brownian diffusion theory, a combination of collision limited reaction rate theory and the bipolar diffusion charging analysis. Comparisons to empirical predictions from the experimental measurements are also made. The study leads to the discovery of a surface-dominated mobility for high aspect ratio nanoparticles with characteristic Knudsen number greater than 5. In view of the extreme relative length scales between particle size and the gas mean free path, particles of all morphologies can be viewed as point collisions; therefore, the equivalent surface mobility diameter is reasonably justified. This finding has been verified in the current study with high aspect ratio particles. For non-spherical particles of more general forms, further investigation is needed. As expected, accuracy of this approximation reduces as the characteristic Knudsen number decreases. When Kn ( dL ) < 0.1, the study shows that particle morphology starts to play an important role. A review of particle mobility for all Knudsen number flows is also provided. © 2017 American Association for Aerosol Research